Sleep and weight loss in low-income overweight or obese postpartum women - Chang, Mei-Wei; Tan, Alai; Schaffir, Jonathan; Wegener, Duane T. (BMC obesity, 2019)
Background We conducted secondary data analyses to examine the associations between sleep duration, sleep quality, sleep disturbance and ≥ 5% of weight loss in low-income overweight or obese postpartum women enrolled in a community-based lifestyle behavior intervention study aimed at prevention of weight gain. Methods Participants were recruited from the Special Supplemental Nutrition Program for Women, Infants, and Children in Michigan. The Pittsburgh Sleep Quality Index was used to assess sleep duration, sleep quality, and sleep disturbance. All participants were assessed and weighed at baseline (T1, 569 participants), 4-month (T2, 367 participants), and 7-month from T1 (T3, 332 participants). Descriptive statistics and mixed-effects regression analysis were performed. Results Participants reported longer sleep duration ( p = 0.048), better sleep quality ( p = 0.003) and less sleep disturbance ( p < 0.001) over time. There were no significant mean body weight changes at T2 and T3. However, a significantly higher proportion of women lost ≥5% of body weight at T3 (23.1%) than T2 (12.5%, p = 0.001). Sleep duration, quality, and disturbance were not significantly associated with ≥5% of weight loss. Conclusion Improvements in sleep duration, sleep quality and sleep disturbance over time were not associated with ≥5% of weight loss in low-income overweight or obese postpartum women. Trial registration Clinical Trials NCT01839708 ; retrospectively registered February 28, 2013.